Critical sensemaking: challenges and promises. Issue 3 (29th August 2019) - Aromaa, Eeva; Eriksson, Päivi; Helms Mills, Jean; Hiltunen, Esa; Lammassaari, Maarit; Mills, Albert J.
Abstract : Purpose: The purpose of this paper is to analyze current literature on critical sensemaking (CSM) to assess its significance and potential for understanding the role of agency in management and organizational studies. Design/methodology/approach: The analysis involves an examination of a selection of 51 applied studies that cite, draw on and contribute to CSM, to assess the challenges and potential of utilizing CSM. Findings: The paper reveals the range of organizational issues that this work has been grappling with; the unique insights that CSM has revealed in the study of management and organizations; and some of the challenges and promises of CSM for studying agency in context. This sets up discussion of organizational issues and insights provided by CSM to reveal its potential in dealing with issues of agency in organizations. The sheer scope of CSM studies indicates that it has relevance for a range of management researchers, including those interested in behavior at work, theories of organization, leadership and crisis management, diversity management, emotion, ethics and justice, and many more. Research limitations/implications: The main focus is restricted to providing a working knowledge of CSM rather than other approaches to agency. Practical implications: The paper outlines the challenges and potential for applying the CSM theory. Social implications: The paper reveals the range of problem-solving issues that CSM studies have been applied to. Originality/value: This is the first major review of the challenges and potential of applying CSM; concluding with a discussion of its strengths and limitations and providing a summary of insights for future work.